Are PARKIN patients ideal candidates for dopaminergic cell replacement therapies?. (23rd January 2019) - Kunath, Tilo; Natalwala, Ammar; Chan, Claire; Chen, Yixi; Stecher, Benjamin; Taylor, Martin; Khan, Sadaquate; Muqit, Miratul M. K.
Abstract: Parkinson's is a heterogeneous, complex condition. Stratification of Parkinson's subtypes will be essential to identify those that will benefit most from a cell replacement therapy. Foetal mesencephalic grafts can alleviate motor symptoms in some Parkinson's patients. However, on‐going synucleinopathy results in the grafts eventually developing Lewy bodies, and they begin to fail. We propose that Parkinson's patients with PARKIN mutations may benefit most from a cell replacement therapy because (a) they often lack synucleinopathy, and (b) their neurodegeneration is often confined to the nigrostriatal pathway. While patients with PARKIN mutations exhibit clinical signs of Parkinson's, post‐mortem studies to date indicate the majority lack Lewy bodies suggesting the nigral dopaminergic neurons are lost in a cell autonomous manner independent of α‐synuclein mechanisms. Furthermore, these patients are usually younger, slow progressing and typically do not suffer from complex non‐nigral symptoms that are unlikely to be ameliorated by a cell replacement therapy. Transplantation of dopaminergic cells into the putamen of these patients will provide neurons with wild‐type PARKIN expression to re‐innervate the striatum. The focal nature of PARKIN‐mediated neurodegeneration and lack of active synucleinopathy in most young‐onset cases makes these patients ideal candidates for a dopaminergic cell replacement therapy. Strategies to improve the outcome of cell replacement therapies for sporadic Parkinson's include the use of adjunct therapeutics that target α‐synuclein spreading and the use of genetically engineered grafts that are resistant to synucleinopathy. Abstract : This diagnosis of Parkinson's disease (PD) can be confirmed by a DAT‐SPECT scan, which is a sensitive measure of dopaminergic nigrostriatal function. If subsequent tests conclude synucleinopathy is not present, and the patient has a pure nigropathy, they should be prioritised for a dopaminergic cell replacement therapy. If synucleinopathy is present, emerging disease‐resistant cell therapies combined with αSyn‐targetted therapeutics could be offered in the near future.